BRIDGING TRADITION AND INNOVATION; NAVIGATING DIGITAL-BASED CHARACTER EDUCATION IN ISLAMIC JUNIOR HIGH SCHOOLS - Muhammad Mahbubi; Amala Bilqis Ahmad; Faiz Faiz; Nadira Rusdiah (Nurul Jadid University, 2025)
The integration of digital technologies into character education presents both opportunities and challenges, particularly in Islamic educational institutions where moral and religious values must be preserved alongside technological advancement. This qualitative comparative case study investigates how SMP Khadijah and SMP Muhammadiyah 4 Pucang implement digital-based character education. Data were collected through interviews, observations, and document analysis involving school leaders, teachers, and students. The findings reveal that SMP Khadijah adopts a structured approach through its 4S Program by utilizing multimedia tools to promote values such as politeness, discipline, and respect. In contrast, SMP Muhammadiyah 4 applies a project-based learning model via its proprietary E-Learning Muhammadiyah (ELMO) platform, encouraging students to produce digital content that reflects values like honesty and tolerance. Both schools face shared challenges, including inconsistent teacher proficiency with digital tools, distractions from non-educational content, and digital literacy gaps among students. Thus, the hybrid model, such as combining teacher-guided structure with student-centered projects it can may offer an effective strategy for embedding character education in digital environments.